10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Domestic ducks are important for meat, egg and livelihood production in Nepal; however, gastrointestinal parasites (GIPs) remain a major health constraint affecting productivity and posing zoonotic risks. This cross-sectional study aimed to determine the prevalence and diversity of GIPs in ducks raised on smallholder farms in Kathmandu, Nepal. Fresh faecal samples (N = 130) were collected randomly using non-invasive methods, and copromicroscopy was performed after direct wet-mount and acid-fast staining techniques. A total of 51 samples (39.2%) tested positive for GIPs. The parasites identified included: Ascaridia galli, Cryptosporidium sp., Eimeria sp., Entamoeba coli, Entamoeba sp., Giardia sp., Strongyle, Taeniid and Tyzzeria sp. A chi-square test (χ2) revealed that the prevalence of protozoa (33.8%) was significantly higher than that of helminths (14.6%) (p < 0.05). Older ducks showed a higher prevalence than young and adult ducks. Additionally, mixed infections were more common than single infections. The findings show that single-celled protozoa, including the zoonotic Cryptosporidium sp., were the primary contributors to higher parasitic infections in ducks than helminths. These findings provide baseline information on duck parasitism and its potential risks to humans. More epidemiological and long-term studies are needed to better understand risk factors, transmission dynamics and the effectiveness of potential parasite control strategies.